Micrology of the sublime (Itinera, 2021)
Starting from the seventeenth-century aesthetic micrology, the essay intends to show how the concept of the sublime has, subterraneously, crossed different cultures configuring itself as that infinitesimal fracture that amazes, an abyssal space in which the moment opens showing us the fragments of what has been essential. From Spinoza to oriental culture, of which haiku is an elected expression, the sublime is not, as Burke claimed, distinct from beauty, but is the origin and the end of beauty. It is an "elevated beauty" and anti-monumental, which lurks in our gaze on the everyday and that, through the poetic intuition of the artist, finds restless and amazed emergence.
Keywords: micrology, haiku, aesthetics, wonder, sublime